Synergistic antidiabetic activity of Taraxacum officinale (L.) Weber ex F.H.Wigg and Momordica charantia L. polyherbal combination - Perumal, Nithiyaa; Nallappan, Meenakshii; Shohaimi, Shamarina; Kassim, Nur Kartinee; Tee, Thiam Tsui; Cheah, Yew Hoong (Elsevier, 2022)
Type 2 Diabetes Mellitus accounts for 90% of most diabetes cases. Many commercial drugs used to treat this disease come with adverse side effects and eventually fail to restore glucose homeostasis. Therefore, an effective, economical and safe antidiabetic remedy from dietary source is considered. Taraxacum officinale (L.) Weber ex F.H.Wigg and Momordica charantia L. were chosen since both are used for centuries as traditional medicine to treat various ailments and diseases. In this study, the antidiabetic properties of a polyherbal combination of T. officinale and M. charantia ethanol extracts are evaluated. The bioactive solvent extracts of the samples selected from in vitro antidiabetic assays; α-amylase, α-glucosidase, and dipeptidyl peptidase-4 (DPP-4) inhibition, and glucose-uptake in L6 muscle cells were combined (1:1) to form the polyherbal combination. The antidiabetic efficacy of polyherbal combination was evaluated employing the above stated in vitro antidiabetic assays and in vivo oral glucose tolerance test and streptozotocin-nicotinamide (STZ-NA) induced diabetic rat model. A quadrupole time-of-flight liquid chromatography-mass spectrometry (Q-TOF LCMS) analysis was done to identify active compounds. The polyherbal combination exerted improved antidiabetic properties; increased DPP-4, α-amylase, and α-glucosidase inhibition. The polyherbal combination tested in vivo on diabetic rats showed optimum blood glucose-lowering activity comparable to that of Glibenclamide and Metformin. This study confirms the polyherbal combination of T. officinale and M. charantia to be rich in various bioactive compounds, which exhibited antidiabetic properties. Therefore, this polyherbal combination has the potential to be further developed as complex phytotherapeutic remedy for the treatment of Type 2 Diabetes Mellitus.